Seasonal growth and needle fall in Pinus sylvestris and P. uncinata - Guerrero-Campo, J.; Camarero, J. J.; Gutierrez, E. (Forest Systems, 1998)
In this work, we study monthly development of tree-ring, elongation of branches, needle fall for Pinus sylvestris L., Pinus uncinata Ram. in the Spanish Central Pyrenees during 1993. Tree-ring formation happens from early June to late September, but most tree-ring growth happens from mid June to mid July. P. sylvestris starts its tree-ring development before P. uncinata. P. uncinata begins its growth of shoots earlier than its tree-ring growth. Needle fall reaches its maximum in autumn. P. uncinata shows a delayed maximum rate of needle fall, a longer period of fall of most of its needles compared to P. sylvestris. This delay, the greater needle dry weight, and the smaller average radial diameter of P. uncinata tracheids compared with P. sylvestris, show P. uncinata adaptations to environments with more stress.